Nutrient status and soil fertility index as a basis for sustainable rice field management in Madiun Regency, Indonesia - Suntoro, Suntoro; Herdiansyah, Ganjar; Mujiyo, Mujiyo (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
Agricultural development, specifically for crops, contributes significantly to national development. However, problems with water and low soil fertility are obstacles to this development. This study evaluated the nutritional status and soil fertility index as the basis for determining the direction of rice field management in Madiun Regency, East Java, Indonesia. The research method was conducted by surveying the soil characteristics followed by laboratory analysis. Soil samples were collected using stratified proportional sampling from 19 land units with 31 samples. The soil fertility index was determined using a principal component analysis test and calculated by dividing the weights by the minimum soil fertility index indicators. The study results show that the nutritional status of total N in the study area is low to high (0.13%–0.59%) and total P is very low to very high (12.18–73.66 ppm), whereas the status of exchangeable K is very low to very high (0.01–0.67 cmol.kg−1), Cation Exchange Capacity is low to high (12.8–36.0 cmol.kg−1), and organic carbon is low to very high (1.98%–6.54%). The soil fertility index ranges from medium to extremely high. The influential indicators are total P, total N, exchangeable K, and organic carbon. It is recommended that the rice field management system implement a “sustainable agricultural intensification” system that combines the two systems “intensification” and “sustainable agroecosystem.” This system still uses proportional inorganic and organic fertilizers (manure, compost, and agricultural waste).